Degenerate cysteine patterns mediate two redox sensing mechanisms in the papillomavirus E7 oncoprotein - Camporeale, Gabriela (2016)
Infection with oncogenic human papillomavirus induces deregulation of cellular redox homeostasis. Virus replication and papillomavirus-induced cell transformation require persistent expression of viral oncoproteins E7 and E6 that must retain their functionality in a persistent oxidative environment. Here, we dissected the molecular mechanisms by which E7 oncoprotein can sense and manage the potentially harmful oxidative environment of the papillomavirus-infected cell. The carboxy terminal domain of E7 protein from most of the 79 papillomavirus viral types of alpha genus, which encloses all the tumorigenic viral types, is a cysteine rich domain that contains two classes of cysteines: strictly conserved low reactive Zn+2 binding and degenerate reactive cysteine residues that can sense reactive oxygen species (ROS). Based on experimental data obtained from E7 proteins from the prototypical viral types 16, 18 and 11, we identified a couple of low pKa nucleophilic cysteines that can form a disulfide bridge upon the exposure to ROS and regulate the cytoplasm to nucleus transport. From sequence analysis and phylogenetic reconstruction of redox sensing states we propose that reactive cysteine acquisition through evolution leads to three separate E7s protein families that differ in the ROS sensing mechanism: non ROS-sensitive E7s; ROS-sensitive E7s using only a single or multiple reactive cysteine sensing mechanisms and ROS-sensitive E7s using a reactive-resolutive cysteine couple sensing mechanism